PERBEDAAN EFEKTIVITAS ANTIBIOTIK PADA TERAPI DEMAM TIFOID DI PUSKESMAS BANCAK KABUPATEN SEMARANG TAHUN 2014 - Risha Fillah Fithria; Kiki Damayanti; Risma Putri Fauziah (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2017)
ABSTRACTThere are differences on the use of antibiotics on typhoid fever’s treatment. However, there was a research concluded that there were no differences between the efficacy of antibiotics on typhoid fever's therapy that shown as fever-free time and treatment duration. The purposes of this study are to determine the various antibiotics that used on typhoid fever’s treatment and to compare the efficacy of that antibiotic at Bancak Public Health Center Semarang regency. This study was an analytically survey research, with retrospective data collection from medical records, used purposive sampling method. The research sample was all adult patients’ typhoid fever hospitalization at Bancak Public Health Center Semarang regency. Data of antibiotic’s efficacy in fever-free time and treatment duration were analyzed with Kruskal-Wallis test. The result showed that the antibiotics used on typhoid fever’s treatment at Bancak Public Health Center Semarang regency were chloramphenicol, amoxicillin, cefotaxime, ceftriaxone, and ampicillin. Ceftriaxone was an antibiotic that provided the shortest fever's free-time and duration of treatment. However, there was no statistically significant difference between efficacy of that antibiotics at Bancak Public Health Center Semarang regency (p>0.05). Key words : Antibiotics efficacy, typhoid fever’s treatment, fever’s free-time, duration of treatment, Bancak Public Health Center.